Long‐term tolerability of capnography and respiratory inductance plethysmography for respiratory monitoring in pediatric patients treated with patient‐controlled analgesia. Issue 10 (3rd June 2015) - Miller, Karen M.; Kim, Andrew Y.; Yaster, Myron; Kudchadkar, Sapna R.; White, Elizabeth; Fackler, James; Monitto, Constance L.; Lonnqvist, Per‐Arne
Summary Background The Anesthesia Patient Safety Foundation has advocated the use of continuous electronic monitoring of oxygenation and ventilation to preemptively identify opioid‐induced respiratory depression. In adults, capnography is the gold standard in respiratory monitoring. An alternative technique used in sleep laboratories is respiratory inductance plethysmography (RIP). However, it is not known if either monitor is well tolerated by pediatric patients for prolonged periods of time. Aim The goal of this study was to determine whether capnography or RIP is better tolerated in nonintubated, spontaneously breathing pediatric patients being treated with intravenous patient‐controlled analgesia (IVPCA). Methods Nasal cannula capnography with oral sampling and thoracic and abdominal inductance plethysmography bands were placed along with the routine monitors on pediatric patients being treated for acute pain with IVPCA. Study monitors were left in place for as long as they were tolerated by the patient, up to a maximum of 24 consecutive hours. If the patient did not wear a particular study monitor for any reason, but tolerated the remaining monitor, participation in the study continued. If the patient would not wear either monitor, participation was terminated. Results Twenty‐six patients (18 female, eight male, average age 10.1 ± 5.5 years) consented to participate, but only 14 patients attempted to wear one or both the devices. Among those who wore either device, median time to device removal was 8.33 h (range 0.3–23.6 h) for capnography and 23.5 h (range 0.7–24 h) for RIP bands. Conclusion Children did not tolerate wearing capnography cannulae for prolonged periods of time, limiting the usefulness of this device as a continuous monitor of ventilation in children. RIP bands were better tolerated; however, they require further assessment of their utility. Until more effective, child‐friendly monitors are developed and their utility is validated, guidelines recommended for adult patients cannot be extended to children.